1994
DOI: 10.1007/bf02000782
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated cat-scratch disease: Detection ofRochalimaea henselae in affected tissue

Abstract: An immunocompetent 9-year-old boy with disseminated cat scratch disease involving spleen, cervical and abdominal lymph nodes, skull, and one clavicle is reported. Antibodies to Rochalimaea quintana and R. henselae were detected, at increasing, then decreasing concentration. DNA extracted from the biopsied skull lesion was amplified by polymerase chain reaction and hybridized with species-specific oligonucleotides proving the presence of R. henselae in affected tissue. Our findings suggest that R. henselae play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 19 publications
0
30
0
1
Order By: Relevance
“…Hepatosplenic abscesses -Hepatosplenomegaly, often associated with fever, has been reported in several papers (Greenbaum et al 1986, Golden 1993, Waldwogel et al 1994, Arisoy et al 1999, Rolain et al 2003. Despite feeling feverish, most patients are not unwell and most give a history of cat exposure.…”
Section: Fever Of Unknown Etiology (Fuo) -Prolonged Fevermentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatosplenic abscesses -Hepatosplenomegaly, often associated with fever, has been reported in several papers (Greenbaum et al 1986, Golden 1993, Waldwogel et al 1994, Arisoy et al 1999, Rolain et al 2003. Despite feeling feverish, most patients are not unwell and most give a history of cat exposure.…”
Section: Fever Of Unknown Etiology (Fuo) -Prolonged Fevermentioning
confidence: 99%
“…Bartonella infections that deserve detailed discussion based on their increasing number of reports include blood culture negative infective endocarditis and fever of unknown origin. In addition, for several decades atypical manifestations of CSD such as meningoencephalitis, retinitis, dissemination with hepatosplenic abscesses and osteomyelitis have been reported, and it is likely that many such manifestations still go unrecognized (Stevens 1952, Adams & Hindman 1954, Selby & Walker 1979, Miller & Bell 1980, Johnson et al 1985, Wear et al 1985, Katner et al 1986, Greenbaum et al 1986, Lewis & Tucker 1986, Margileth et al 1987, Chrousous et al 1990, Apalsch et al 1993, Golden 1993, Tappero et al 1993, Bernini et al 1994, Waldwogel et al 1994, Hadley et al 1995, Whitman & Krafte-Jacobs 1995, Riviello & Ruoff 1998, Walter & Eppes 1998, Arisoy et al 1999, Hulzebos et al 1999, Robson et al 1999, Azevedo et al 2000, Krause et al 2000, Hmaimess et al 2004, Baylor et al 2007, Stockmeyer et al 2007). The onset of signs and symptoms of bartonellosis generally occur about one to two weeks after exposure, but this delay can range from 1-4 weeks, depending on the syndrome presented, and may last several months (Carithers 1985).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Moreover, histopathological analysis is only possible after surgical biopsy. Recently, the detection ofBartonella (Rochalimaea) henselae in affected tissue has suggested that this fastidious bacterium is a causative agent of CSD [2,9]. Although serological tests to detect specific antibodies to B. henselae have been developed [6,7], their value in supplanting the traditional diagnostic criteria for CSD is not clear.…”
Section: Introductionmentioning
confidence: 98%
“…Como se observó en esta niña, y también en otros casos publicados 21,33 , el compromiso óseo puede ocurrir tardíamente, semanas o meses después de la resolución clínica del cuadro.…”
Section: Discussionunclassified